Quantum-enhanced sensing based on time reversal of nonlinear dynamics - Linnemann, Daniel; Strobel, Helmut; Müssel, Wolfgang; Schulz, Jessica; Lewis-Swan, R. J.; Kheruntsyan, K. V.; Oberthaler, Markus K. (Physical review letters, 2016)
We experimentally demonstrate a nonlinear detection scheme exploiting time-reversal dynamics that disentangles continuous variable entangled states for feasible readout. Spin-exchange dynamics of Bose-Einstein condensates is used as the nonlinear mechanism which not only generates entangled states but can also be time reversed by controlled phase imprinting. For demonstration of a quantum-enhanced measurement we construct an active atom SU(1,1) interferometer, where entangled state preparation and nonlinear readout both consist of parametric amplification. This scheme is capable of exhausting the quantum resource by detecting solely mean atom numbers. Controlled nonlinear transformations widen the spectrum of useful entangled states for applied quantum technologies.